Нові дослідження замчища Б. Хмельницького у Суботові - Куштан, Д.П. (Археологічні дослідження в Україні, 2009)
The paper presents the results of the archaeological excavations undertaken on the multilayer hill-fort and castle area of B. Khmelnytskyi in Subotiv village of Chyhyryn Region in Cherkasy Oblast in 2008. During the research the new materials describing history of the development of the archaeological site since the Bronze age until the Late Mediaeval period have been discovered.